Weighted iterated radial composition operators from logarithmic Bloch spaces to weighted‐type spaces on the unit ball. (21st November 2021) - Stević, Stevo; Jiang, Zhi‐jie
Abstract : Let M u be the multiplication operator with symbol u which is a holomorphic function on the open unit ball 𝔹 in ℂ n, C φ the composition operator with symbol φ which is a holomorphic self‐map of 𝔹, and ℜ m, m ∈ ℕ, the m th iterated radial derivative operator. The boundedness and compactness of the weighted iterated radial composition operator ℜ u, φ m : = M u C φ ℜ m from logarithmic Bloch spaces to weighted‐type spaces are characterized.